Comparison of the Prevalence of Space Maintainers among Different Age Groups and Genders in Children - S.Vignesh, Vignesh Ravindran, Arvina Rajasekar (Institute of Medico-legal Publications Pvt Ltd, 2020)
The space maintainers are mainly the devices that have been specially designed to maintain a space or tocreate an additional space that was lost due to the premature loss of the primitive teeth. They are mainlyavailable in the various types with different types of indications. The main reasons for the premature lossof the teeth has been indicated for the extraction due to the dental caries or trauma or any type of geneticdisorders.The main aim of this study is to estimate the most common type of the space maintainer that hasbeen used among the different age and gender groups. All the patients are being considered in the studywith the age group of 3-12 years, they must mainly have clinically missing teeth. The results are obtainedand tabulated for the statistical analysis, both descriptive and inferential test which is done by using SPSSversion 23. From the above study the results are obtained as, the age distribution of this particular study ismainly about the age groups 1-5 years(48%) and 6-12 years (52%),the gender distribution of this study ismales(62%) and females (38%). The most common type of the space maintainer used is the Band and loopspace maintainer. Within the limits of this particular study the most common type of the space maintainerindicated is the band and loop space maintainer for the age group of 6-12 years and has the higher genderpredilection among the male children.